An All‐Inorganic, Transparent, Flexible, and Nonvolatile Resistive Memory - Yuxi Yang; Wenxiu Gao; Zhongshuai Xie; Yaojin Wang; Guoliang Yuan; Jun‐Ming Liu (Advanced Electronic Materials, 2018)
Abstract A rapid surge in the research of lightweight, invisible, and flexible electronics is occurring with the arrival of Internet of Things (IoT). However, multifunctional perovskite oxide electronics are commonly hard and should be synthesized at high temperature and oxygen ambience, where most transparent conductive films will become brittle or highly resistive. Thus, the realization of transparent and flexible nonvolatile perovskite oxide resistive memory remains a big challenge. Here, a transparent, flexible, nonvolatile, and all‐inorganic memory with the mica substrate is prepared: the 2.7 wt% Ag‐doped indium–tin oxide (Ag–ITO) film as bottom electrodes, the BaTi0.95Co0.05O3−δ (BTCO) film as resistive‐switching functional layer, and the Ag/ITO films as top electrodes. The Ag–ITO/BTCO/Ag/ITO heterosturcture shows a unipolar resistive‐switching behavior, and its high/low resistance ratio is up to 5 × 103 under a low operating voltage (<2.8 V) with fast response speed (≈50 ns). Either high‐ or low‐resistance states remain stable even after the 14 400 cycles' dynamic bending test with the minimum radius of 3 mm. Additionally, the bipolar resistive‐switching characteristic is observed in the ≈85 nm diameter region. As a result, such resistive memory shows potential to be used in many transparent and flexible devices, such as electronic skins and flexible displays.